Dampak Pengaruh Kurs Valuta Asing Dan Inflasi Terhadap Jakarta Islamic Index - Muhtadi, Ridan; Rizatul Yunus, Muhammad; Maulia, Shirenda Rizka; Fudholi, Moh. (LP2M IAI Miftahul Ulum Pamekasan, 2021)
Jakarta Islamic Index (JII) is one of the sharia-based stock indexes in Indonesia that provides benefits for capital owners to make investments in accordance with Islamic sharia on the Stock Exchange. This study aims to analyze the Effect of Foreign Exchange Rate Fluctuations (US Dollar and Euro) and Inflation on the Jakarta Islamic Index (JII), with an observation period during July 2017-August 2019. The data used in this study is time series data that is quantitative. which consists of data on the monthly closing value of the JII Variable, Inflation and data on the monthly closing value of the Rupiah exchange rate against the Dollar and EURO. The analytical method used is Multiple Linear Analysis, Hypothesis Testing, and Coefficient of Determination Test. The data processing is carried out using the SPSS 20.0 application. Based on the results of the t test, it partially shows that the value of the US Dollar Exchange Rate (US) variable has a positive and not significant effect, the EURO exchange rate variable has a positive and insignificant effect while the inflation variable has a positive and insignificant effect on the Jakarta Islamic Index in the 2017-2019 period. . Variables US, EURO, and inflation simultaneously or together do not have a positive and significant effect on the stock of the Jakarta Islamic Index.